Enhancing Structural Health Monitoring for structures subjected to time-variant operating conditions - Casper Aaskov Drangsfeldt; Luis David Avendano-Valencia; Marie Lützen (Research and Review Journal of Nondestructive Testing)
The expected growth of new offshore wind turbine installations necessitates